Improving running-in quality and efficiency of journal bearing with ZB and SiO2 nanoparticles as lubricant additive. (1st September 2022) - Zhou, Yuankai; Wang, Zhiyong; Wang, Jiabiao; Zuo, Xue; Xu, Jing
Abstract: To both improve the running-in quality and efficiency of the journal bearing, the Zinc borate and SiO2 combinations (ZB/SiO2 ) are used as lubricant additive. Running-in tests were carried out using a ring-on-block tribometer. Multifractal parameters and correlation dimensions were used to extract the nonlinear characteristics of surface topography and coefficient of friction (COF), respectively. It is also used to evaluate the running-in quality of journal bearing. The time of correlation dimension to reach the stable stage is used to evaluate the running-in efficiency. With the addition of ZB/SiO2, the correlation dimension of COF increases and the multifractal parameters of wear surfaces decrease significantly. Compared with the single ZB or SiO2 additive, the running-in efficiency of the ZB/SiO2 additive can be improved by 25% and 40%, respectively. It indicates that the running-in quality and efficiency are improved with the additive of ZB/SiO2 . The excellent tribological properties of ZB/SiO2 are attributed to the solid lubricating film formed by ZB, as well as the rolling, self-repairing, and polishing effect of SiO2 . The results are of great significance to improving the service reliability and extending the service life of the journal bearing.